Positive electrode active material, preparation method, positive electrode and battery
By forming a composite cladding layer of MXene material and metal oxide on the surface of the lithium manganate positive electrode active material, the problem of material crushing during rolling and circulation is solved, the cycle stability and ion transport performance are improved, and the cycle performance and rate performance of the battery are improved.
Patent Information
- Application Number
- CN202411796088.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The existing lithium manganate positive electrode active material is prone to shatter during rolling and battery circulation, resulting in slow lithium ion transmission speed, low compaction density, and manganese ions dissolution when in contact with the electrolyte, resulting in deterioration of battery circulation performance.
By forming a composite cladding layer of MXene material and metal oxide on the surface of single-crystalline lithium manganate and secondary spherical lithium manganate, the material is prevented from breaking during rolling and circulation, and the lithium ion transfer speed and compaction density are improved.
Effectively prevent the crushing of lithium manganese oxide materials, improve circulation stability and ion transmission performance, enhance the stability of the positive electrode interface, form a more stable CEI film, isolate the electrolyte and lithium manganese oxide materials, and improve the circulation and rate performance of the battery.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium-ion batteries, and in particular to a positive electrode active material, a preparation method, a positive electrode, and a battery. Background Art
[0002] Lithium manganate (LiMn2O4) as a positive electrode active material has the advantages of low price, high potential, environmental friendliness and high safety performance. advantage, Commonly used lithium manganese oxide can be divided into secondary spherical lithium manganese oxide, quasi-single crystal lithium manganese oxide, and single crystal lithium manganese oxide according to their structure; single crystal lithium manganese oxide has a lower capacity, a larger particle size, and a slow lithium ion transmission rate, while secondary spherical lithium manganese oxide particles have a higher capacity but a lower compaction density, and quasi-single crystal lithium manganese oxide has a tight structure, a small exposed area, a smaller particle size, and a faster lithium ion transmission rate. However, both secondary spherical lithium manganese oxide particles and quasi-single crystal lithium manganese oxide will break during rolling and long-term battery cycling, increase the contact area between the particles and the electrolyte, and cause manganese ions to dissolve, resulting in deterioration of battery cycle performance.
[0003] Therefore, developing a lithium manganese oxide composite material with both high compaction density and structural stability to obtain a lithium ion battery with superior performance is a technical problem that urgently needs to be solved in this field. Summary of the invention
[0004] The object of the present invention is to provide a positive electrode active material and a preparation method thereof, a positive electrode and a battery, comprising quasi-single-crystal lithium manganate and secondary spherical lithium manganate with coating layers formed on their surfaces respectively. On the one hand, by combining the quasi-single-crystal lithium manganate and the secondary spherical lithium manganate, the compaction density of the electrode can be increased and the migration speed of lithium ions can be increased; on the other hand, by forming a coating layer resistant to HF corrosion on the surface of the quasi-single-crystal lithium manganate and the secondary spherical lithium manganate, the coating can effectively prevent the quasi-single-crystal lithium manganate and the secondary spherical lithium manganate from being broken or even structurally destroyed during the rolling process and the subsequent charge and discharge cycle process, and can also prevent HF in the electrolyte from corroding the coating layer and causing coating failure.
[0005] The technical solution of the present invention is achieved in this way:
[0006] In a first aspect, the present application provides a positive electrode active material, including a first positive electrode active material and a second positive electrode active material;
[0007] The first positive electrode active material includes quasi-single-crystal lithium manganese oxide and a coating layer coated on the surface of the quasi-single-crystal lithium manganese oxide;
[0008] The second positive electrode active material includes secondary spherical lithium manganese oxide and a coating layer coated on the surface of the secondary spherical lithium manganese oxide;
[0009] The coating layer includes MXene material and metal oxide.
[0010] In one embodiment, the MXene material includes any one of Ti3C2Tx, Nb2CTx, Ta4C3Tx or V4C3Tx, or a combination of at least two thereof.
[0011] In one embodiment, the sum of the masses of the quasi-single-crystal lithium manganate and the secondary spherical lithium manganate is m0, and the mass of the MXene material is m1, then m0 and m1 satisfy m1 / m0=0.1% to 1%.
[0012] In one embodiment, the metal oxide includes at least one of MgO, Al2O3, Nb2O5, ZrO2, and WO3.
[0013] In one embodiment, the sum of the masses of the quasi-single-crystal lithium manganese oxide and the secondary spherical lithium manganese oxide is m0, and the mass of the metal oxide is m2, then m0 and m2 satisfy m2 / m0=0.1% to 1%.
[0014] In one embodiment, the coating layer has a thickness of 10-100 nm.
[0015] In one embodiment, the particle size D50 of the secondary spherical lithium manganese oxide is larger than the particle size D50 of the quasi-single-crystalline lithium manganese oxide.
[0016] In one embodiment, the particle size D50 of the secondary spherical lithium manganese oxide is 7-10 μm.
[0017] In one embodiment, the particle size D50 of the quasi-single-crystal lithium manganese oxide is 1-3 μm.
[0018] In one embodiment, the general formula of the quasi-single-crystal lithium manganese oxide is Li 1+a Mn 2-a-b-c Al b B c O4; among which, 0.001≤a≤0.30, 0.001≤b≤0.2, 0.001≤c≤0.1.
[0019] In one embodiment, the general formula of the secondary spherical lithium manganate is Li 1+x Mn 2-x-y M y O4; wherein, 0.001≤x≤0.20, 0.001≤y≤0.3, and M includes at least two of Mg, Al, Nb, and Co.
[0020] In a preferred embodiment, the M includes two of Al, Nb and Co.
[0021] In one embodiment, the mass ratio of the quasi-single-crystal lithium manganese oxide to the secondary spherical lithium manganese oxide is (1-4):(9-6).
[0022] In a second aspect, the present application provides a method for preparing a positive electrode active material as described in the first aspect, comprising the following steps:
[0023] 1) uniformly mixing the quasi-single-crystal lithium manganate and the secondary spherical lithium manganate to form a first mixture;
[0024] 2) mixing the first mixture, MXene material, metal oxide and solvent to obtain a mixed solution;
[0025] 3) spray drying the mixed solution to obtain a positive electrode active material.
[0026] In one embodiment, the step 1) includes uniformly mixing the quasi-single-crystal lithium manganate and the secondary spherical lithium manganate in a mass ratio of (1-4):(9-6).
[0027] In one embodiment, in the step 2), the mass ratio of the MXene material to the first mixture is 0.1 to 1:100.
[0028] In one embodiment, in the step 2), the mass ratio of the metal oxide to the first mixture is 0.1 to 1:100.
[0029] In one embodiment, in the step 2), the solvent includes one of an ethanol solution, NMP or a propanol solution.
[0030] In one embodiment, the step 2) includes stirring and mixing the first mixture, MXene material, metal oxide and solvent to obtain a mixed solution, wherein the stirring time is 2 to 8 hours.
[0031] In one embodiment, in step 3), the inlet temperature of the spray drying is 200-400°C, and the outlet temperature is 50-100°C.
[0032] In a third aspect, the present application provides a positive electrode, comprising the positive electrode active material as described in the first aspect.
[0033] In a fourth aspect, the present application provides a battery, comprising the positive electrode active material as described in the first aspect or the positive electrode as described in the third aspect.
[0034] Compared with the prior art, the beneficial effect of the present invention is that: by forming a coating layer on the surface of the quasi-single-crystalline lithium manganese oxide and the secondary spherical lithium manganese oxide, the present application can effectively prevent the quasi-single-crystalline lithium manganese oxide and the secondary spherical lithium manganese oxide from particle breakage during rolling and in the cycle of the battery, thereby ensuring the cycle stability of the lithium manganese oxide material and ensuring the good ion transmission performance of the quasi-single-crystalline lithium manganese oxide material.
[0035] The coating layer is a composite coating layer of MXene material and metal oxide. These two materials have good pressure resistance, which prevents the damage of single-crystal lithium manganese oxide and secondary spherical lithium manganese oxide by rolling. On the other hand, both materials are resistant to HF corrosion, ensuring the stability of the positive electrode interface, so that the modified interface can form a more stable CEI film during the charge and discharge process, and achieve a better isolation effect on the electrolyte and lithium manganese oxide material; thirdly, the MXene material and metal oxide cooperate synergistically, which is conducive to improving the ionic conductivity of the coating layer.
[0036] The coated quasi-single-crystal lithium manganese oxide and secondary spherical lithium manganese oxide are mixed. Since the two have a certain difference in particle size, the small quasi-single-crystal lithium manganese oxide particles can be evenly filled into the gaps between the large secondary spherical lithium manganese oxide particles. Then, the combination of the two can effectively improve the compaction density of the positive electrode active material. DETAILED DESCRIPTION
[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specific implementation methods are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the description and claims of the present invention are intended to cover non-exclusive inclusions.
[0039] In the description of the specific implementation methods of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0040] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.
[0041] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects before and after are in an "or" relationship.
[0042] Throughout the present invention, numerical values represent approximate measures or limits of ranges to cover minor deviations from given values as well as embodiments with about the values mentioned and embodiments with the exact values mentioned. Except for the working examples provided at the end of the detailed description, all numerical values of parameters (e.g., amounts or conditions) in this specification (including the appended claims) should be understood to be modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value. "About" indicates that the stated numerical value allows some minor imprecision (close to the exact value of the value to some extent; approximately or reasonably close to the value; almost). If the imprecision provided by "about" is not otherwise understood in this ordinary sense in the art, "about" as used in the present invention at least indicates the variation that can be produced by the ordinary methods of measuring and using such parameters. For example, "about" may include a variation of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some aspects, optionally less than or equal to 0.1%.
[0043] Additionally, disclosure of ranges includes disclosure of all values within the entire range and further divided ranges, including endpoints and sub-ranges given for such ranges.
[0044] Because lithium manganese oxide materials and electrolytes are prone to side reactions, the trivalent manganese ions in the lithium manganese oxide materials undergo a disproportionation reaction. The generated divalent manganese ions easily move to the negative electrode side, undergo a reduction reaction at the negative electrode, and are deposited on the negative electrode side, continuously destroying the SEI film, causing the SEI film to be continuously destroyed and regenerated, consuming lithium ions and causing the battery's cycle performance to deteriorate.
[0045] On the other hand, the commonly used lithium manganese oxide materials currently have problems in different aspects. Based on the requirements for capacity performance and rate performance, the present application adopts single-crystal lithium manganese oxide and secondary spherical lithium manganese oxide for use in combination. At the same time, the coating can not only effectively avoid the structural damage and particle breakage that may occur in the rolling process and subsequent charge and discharge cycles of the single-crystal lithium manganese oxide and the secondary spherical lithium manganese oxide, but also effectively isolate the contact between the electrolyte and the lithium manganese oxide. At the same time, through the selection of the coating material, the stability of the positive electrode interface is ensured, so that the modified interface can form a more stable CEI film during the charge and discharge process.
[0046] The technical solution of the present invention is achieved in this way:
[0047] In a first aspect, the present application provides a positive electrode active material, including a first positive electrode active material and a second positive electrode active material;
[0048] The first positive electrode active material includes quasi-single-crystal lithium manganese oxide and a coating layer coated on the surface of the quasi-single-crystal lithium manganese oxide;
[0049] The second positive electrode active material includes secondary spherical lithium manganese oxide and a coating layer coated on the surface of the secondary spherical lithium manganese oxide;
[0050] In one embodiment, the coating layer includes MXene material and metal oxide.
[0051] The present application forms a coating layer on the surface of the quasi-single-crystal lithium manganate and the secondary spherical lithium manganate, which can effectively prevent the quasi-single-crystal lithium manganate and the secondary spherical lithium manganate from particle breakage during rolling and in the cycle of the battery, thereby ensuring the cycle stability of the lithium manganate material and ensuring the good ion transmission performance of the quasi-single-crystal lithium manganate material.
[0052] The coating layer is a composite coating layer of MXene material and metal oxide, both of which have good pressure resistance, preventing the damage of single-crystal lithium manganese oxide and secondary spherical lithium manganese oxide by rolling. On the other hand, both are resistant to HF corrosion, ensuring the stability of the positive electrode interface, so that the modified interface can form a more stable CEI film during the charge and discharge process; thirdly, the MXene material and metal oxide cooperate synergistically, which is conducive to improving the ionic conductivity of the coating layer.
[0053] In one embodiment, the MXene material includes any one of Ti3C2Tx, Nb2CTx, Ta4C3Tx or V4C3Tx, or a combination of at least two thereof.
[0054] In one embodiment, the sum of the masses of the quasi-monocrystalline lithium manganate and the secondary spherical lithium manganate is m0, and the mass of the MXene material is m1, then m0 and m1 satisfy m1 / m0=0.1% to 1%. Specifically, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%. Of course, it can also be any value within this range, and the present invention does not impose any limitation on this.
[0055] In one embodiment, the metal oxide includes at least one of MgO, Al2O3, Nb2O5, ZrO2, and WO3.
[0056] In one embodiment, the sum of the mass of the quasi-monocrystalline lithium manganate and the secondary spherical lithium manganate is m0, and the mass of the metal oxide is m2, then m0 and m2 satisfy m2 / m0=0.1% to 1%. Specifically, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%. Of course, it can also be any value within this range, and the present invention does not impose any limitation on this.
[0057] In one embodiment, the thickness of the coating layer is 10-100 nm. Specifically, it can be 10 nm, 25 nm, 40 nm, 55 nm, 70 nm, 85 nm, 100 nm. Of course, it can also be any value within this range, and the present invention does not impose any limitation on this.
[0058] In one embodiment, the particle size D50 of the secondary spherical lithium manganese oxide is larger than the particle size D50 of the quasi-single crystal lithium manganese oxide.
[0059] In one embodiment, the particle size D50 of the secondary spherical lithium manganate is 7-10 μm. Specifically, it can be 7 μm, 7.6 μm, 8 μm, 8.3 μm, 9 μm, 9.5 μm, 10 μm. Of course, it can also be any value within this range, and the present invention does not impose any limitation on this.
[0060] In one embodiment, the particle size D50 of the quasi-single-crystal lithium manganate is 1-3 μm. Specifically, it can be 1 μm, 1.2 μm, 1.8 μm, 2 μm, 2.5 μm, 2.7 μm, or 3 μm. Of course, it can also be any value within this range, and the present invention does not impose any limitation on this.
[0061] In one embodiment, the general formula of the quasi-single-crystal lithium manganese oxide is Li 1+a Mn 2-a-b-c Al b B c O4; among which, 0.001≤a≤0.30, 0.001≤b≤0.2, 0.001≤c≤0.1.
[0062] It can be understood that by simultaneously doping the lithium manganese oxide material with Al and B, it is beneficial to improve the lattice stability of the lithium manganese oxide material and the cycle stability of the material, and B doping is beneficial to lowering the melting point of the lithium manganese oxide material and forming a single-crystal-like material.
[0063] In one embodiment, the general formula of the secondary spherical lithium manganate is Li 1+x Mn 2-x-y M y O4; wherein, 0.001≤x≤0.20, 0.001≤y≤0.3, and M includes at least two of Mg, Al, Nb, and Co.
[0064] In a preferred embodiment, M includes two of Al, Nb and Co.
[0065] Doping with multiple elements is beneficial to further improve the structural stability of the lithium manganese oxide material.
[0066] In one embodiment, the mass ratio of the quasi-single-crystal lithium manganate to the secondary spherical lithium manganate is (1-4):(9-6). Specifically, it can be 1:9, 2:8, 2:7, 3:7, 4:6. Of course, it can also be any value within this range, and the present invention does not impose any limitation on this.
[0067] It can be understood that the mass of the quasi-single-crystal lithium manganese oxide is less than that of the secondary spherical lithium manganese oxide, which is beneficial for the positive electrode active material to provide a higher capacity.
[0068] In a second aspect, the present application provides a method for preparing a positive electrode active material as in the first aspect, comprising the following steps:
[0069] 1) uniformly mixing the quasi-single-crystal lithium manganate and the secondary spherical lithium manganate to form a first mixture;
[0070] 2) mixing the first mixture, the MXene material, the metal oxide and the solvent to obtain a mixed solution;
[0071] 3) The mixed solution is spray-dried to obtain a positive electrode active material.
[0072] In one embodiment, step 1) includes uniformly mixing the quasi-single-crystal lithium manganate and the secondary spherical lithium manganate in a mass ratio of (1-4):(9-6).
[0073] In one embodiment, in step 2), the mass ratio of the MXene material to the first mixture is 0.1 to 1:100.
[0074] In one embodiment, in step 2), the mass ratio of the metal oxide to the first mixture is 0.1-1:100.
[0075] In one embodiment, in step 2), the solvent includes one of ethanol solution, NMP or propanol solution.
[0076] In one embodiment, step 2) includes stirring and mixing the first mixture, MXene material, metal oxide and solvent to obtain a mixed solution, wherein the stirring time is 2 to 8 hours.
[0077] In one embodiment, in step 3), the inlet temperature of the spray drying is 200-400°C, and the outlet temperature is 50-100°C.
[0078] In one embodiment, step 1) further includes the preparation of quasi-single-crystal lithium manganate, including the following steps:
[0079] Mixing a spherical or quasi-spherical metal oxide or sulfate containing a Mn precursor, a lithium source, an Al source, and a B source uniformly according to a stoichiometric ratio;
[0080] After calcination in air, single-crystal lithium manganate powder is obtained.
[0081] In a preferred embodiment, the Mn-containing precursor includes one of manganese tetraoxide, manganese trioxide, or manganese carbonate, or a mixture of the two.
[0082] In a preferred embodiment, the lithium source is lithium carbonate, lithium hydroxide or a mixture of the two.
[0083] In a preferred embodiment, the Al source is Al2O3 or Al(OH)3.
[0084] In a preferred embodiment, the B source is H3BO3.
[0085] In a preferred embodiment, in the step of obtaining the single-crystal-like lithium manganate powder by calcining in an air atmosphere, the calcination temperature is 600-900° C. and the calcination time is 8-20 hours.
[0086] In one embodiment, step 1) further includes preparing secondary spherical lithium manganate, comprising the following steps:
[0087] A spherical or quasi-spherical Mn-containing precursor, a lithium source, and a metal oxide or sulfate of a metal M source are uniformly mixed according to a stoichiometric ratio;
[0088] After calcination in air, secondary spherical lithium manganate powder is obtained.
[0089] In one embodiment, the calcination temperature is 400-800° C., and the calcination time is 8-20 hours.
[0090] In one embodiment, the metal M includes at least two of Mg, Al, Nb, and Co.
[0091] In a preferred embodiment, the metal M includes at least two of Al, Nb, and Co.
[0092] In a third aspect, the present application provides a positive electrode, comprising the positive electrode active material of the first aspect.
[0093] In one embodiment, the positive electrode includes a positive electrode layer.
[0094] In some embodiments, the positive electrode layer further includes a binder, which improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode material layer and the positive electrode current collector.
[0095] In some embodiments, non-limiting examples of binders include polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.
[0096] In some embodiments, the positive electrode layer includes a conductive agent to impart conductivity to the electrode. The conductive agent may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0097] In some embodiments, based on the total mass of the positive electrode layer, the mass percentage of the positive electrode active material in the positive electrode layer is 80%-99%.
[0098] In some embodiments, the mass of the conductive agent accounts for 1%-20% of the mass of the positive electrode layer.
[0099] In some embodiments, the mass of the binder accounts for 1%-20% of the mass of the positive electrode layer.
[0100] In some embodiments, the positive electrode layer provided by the present invention further includes solid electrolyte powder for improving the ionic conductivity of the positive electrode layer. The present invention does not limit the type of solid electrolyte powder, which may be oxide solid electrolyte powder, sulfide solid electrolyte powder, or halide solid electrolyte powder. Optionally, the mass of the solid electrolyte powder accounts for 1%-20% of the mass of the positive electrode layer; preferably 5%-20%.
[0101] In some embodiments, the thickness of the positive electrode layer in the positive electrode provided by the present invention is 30-400 μm, for example, 30 μm, 40 μm, 50 μm, 80 μm, 110 μm, 200 μm, 300 μm, 400 μm, preferably 50-110 μm.
[0102] In some embodiments, the positive electrode includes a positive electrode current collector. Exemplarily, the positive electrode current collector may be aluminum (Al), but is not limited thereto.
[0103] In a fourth aspect, the present application provides a battery, comprising the positive electrode active material of the first aspect or the positive electrode of the third aspect.
[0104] In one embodiment, the battery further includes a negative electrode plate, a separator and an electrolyte.
[0105] Negative electrode:
[0106] In some embodiments, the negative electrode sheet includes a current collector and a negative active material layer disposed on the current collector.
[0107] In the present invention, the specific types of negative electrode active materials are not subject to specific restrictions and can be selected according to needs. Specifically, the negative electrode active material is selected from natural graphite, artificial graphite, mesophase microcarbon beads (MCMB for short), hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy. Non-limiting examples of carbon materials include crystalline carbon, amorphous carbon and mixtures thereof. Crystalline carbon can be amorphous or flake-shaped, platelet-shaped, spherical or fibrous natural graphite or artificial graphite. Amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc.
[0108] In some embodiments, metal elements and metal compounds can also be selected as negative electrode active materials, such as compounds containing metals or metalloids such as Li, Ag, Al, Bi, Cu, Ga, Ge, In, Ni, Pb, Sb, Si, Sn, Sr, and Zn.
[0109] In some embodiments, the mass percentage of the negative electrode active material contained in the negative electrode active material layer may be 80%-99%, for example, 80%, 85%, 90%, 95%, 97%, 99%, etc., preferably 95%-97%.
[0110] In some embodiments, the negative electrode material layer may include a binder; the binder improves the bonding between negative electrode active material particles and the bonding between the negative electrode active material and the current collector.
[0111] In some embodiments, non-limiting examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.
[0112] In some embodiments, the negative electrode active material layer can be obtained by coating a negative electrode slurry on a negative electrode current collector and then drying the negative electrode slurry, wherein the negative electrode slurry includes at least a negative electrode active material and a negative electrode binder. When an aqueous solvent is used as a liquid medium for forming the negative electrode slurry, a thickener is preferably used for slurrying, and the thickener can generally be used to adjust the viscosity of the slurry.
[0113] In some embodiments, the aforementioned viscosity enhancer may be one or more of the following: carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof.
[0114] In some embodiments, the mass proportion of the thickener in the negative electrode slurry can be 0.1%-5%, for example, 0.1%, 0.2%, 0.5%, 0.6%, 1%, 2%, 3%, 4%, 5%, etc., preferably 0.5%-3%, and more preferably 0.6%-2%.
[0115] In some embodiments, the negative electrode active material layer includes a conductive material so that the electrode has conductivity. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., such as copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0116] In some embodiments, the negative electrode current collector can be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.
[0117] Diaphragm:
[0118] In some embodiments, the lithium battery and electrochemical device of the present invention are provided with a separator between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator used in the electrochemical device of the present invention are not particularly limited and can be any technology disclosed in the prior art.
[0119] In some embodiments, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0120] In some embodiments, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide.
[0121] Electrolyte:
[0122] The lithium battery and electrochemical device of the present invention also include an electrolyte.
[0123] In some embodiments, the electrolyte includes a lithium salt and a solvent.
[0124] In some embodiments, the lithium salt includes at least one of an organic lithium salt or an inorganic lithium salt. In some embodiments, the lithium salt includes, but is not limited to, lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (LiFSI), lithium bis(oxalatoborate) LiB(C2O4)2 (LiBOB), or lithium di(oxalatoborate) LiBF2(C2O4) (LiDFOB).
[0125] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0126] In some embodiments, the electrolyte may optionally include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.
[0127] In some embodiments, the aforementioned additives include at least one of 1,3-propane sultone, 1,4-butane sultone, propenyl-1,3-sultone, vinyl sulfate, 4-methyl vinyl sulfate, propenyl sulfate, saturated phosphate compounds and unsaturated phosphate compounds, tris(trimethylsilane) phosphate, tris(trimethylsilane) borate, tris(triethylsilane) borate, succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile, and sebaconitrile, and a compound comprising the following chemical formula:
[0128]
[0129] Among them, R 41 , R 42 , R 43 Each independently selected from a C1-C5 saturated hydrocarbon group, an unsaturated hydrocarbon group, a halogenated hydrocarbon group, -Si(C m H2m+1 )3, m is a natural number from 1 to 3, and R 41 , R 42 , R 43 At least one of them is an unsaturated hydrocarbon group.
[0130] In some embodiments, the secondary battery according to the present invention is made by stacking the above-mentioned positive and negative electrode sheets.
[0131] In some embodiments, the secondary battery of the present invention may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0132] In some embodiments, the present invention further provides a battery module. The battery module includes the above-mentioned secondary battery. The number of secondary batteries contained in the battery module of the present invention can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0133] In some embodiments, the present invention further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0134] The following is an explanation of the embodiments of the present invention according to the technical content of the present invention, but it should not be limited to the following embodiments 1
[0135] 1. Preparation of positive electrode active materials:
[0136] 1) Preparation of single-crystal lithium manganate:
[0137] The manganese-containing precursor Mn3O4, the lithium source Li2CO3, H3BO3 and the metal oxide Al2O3 are uniformly mixed according to the stoichiometric ratio;
[0138] After calcination at 750℃ in air for 20 hours, single-crystal lithium manganate Li 1.1 Mn 1.75 Al 0.1 B 0.05 O4;
[0139] The particle size D50 of the single-crystal lithium manganate is 2 μm.
[0140] 2) Preparation of secondary spherical lithium manganate:
[0141] The manganese-containing precursor Mn3O4, the lithium source Li2CO3 and the metal oxides Al2O3 and Nb2O5 are uniformly mixed according to the stoichiometric ratio;
[0142] After calcination at 650℃ in air for 16 hours, secondary spherical lithium manganate Li 1.05 Mn 1.84 Al 0.1 Nb 0.01 O4;
[0143] The particle size D50 of the secondary spherical lithium manganate is 9 μm.
[0144] 3) Preparation of positive electrode active material: mixing the quasi-single-crystal lithium manganate and the secondary spherical lithium manganate in a mass ratio of 2:8 to form a first mixture;
[0145] The first mixture, Ti3C2T x , WO3 and solvent NMP were stirred and mixed for 6 hours to obtain a mixed solution; wherein Ti3C2T x The mass ratio of WO3 to the first mixture is 0.5:100; the mass ratio of WO3 to the first mixture is 0.5:100.
[0146] The mixed solution is spray-dried to obtain a positive electrode active material, wherein the positive electrode active material includes a first positive electrode active material and a second positive electrode active material.
[0147] 2. Preparation of positive electrode:
[0148] The positive electrode active material, conductive agent Super-P, and binder PVDF were weighed and mixed evenly in a mass ratio of 95:2:3, mixed with solvent NMP to obtain a positive electrode slurry, and evenly coated on an aluminum foil, dried, and rolled to form a positive electrode.
[0149] Preparation of negative electrode: The negative electrode active material graphite, conductive agent Super-P, binder CMC, and SBR are weighed and mixed evenly in a mass ratio of 95:3:1:1, mixed with solvent deionized water to obtain negative electrode slurry, evenly coated on copper foil, dried, and rolled to form a negative electrode.
[0150] The electrolyte composition: solvent propylene carbonate and lithium salt LiPF6, the concentration of the electrolyte salt is 1 mol / L.
[0151] Battery preparation: Assemble the positive electrode, negative electrode and separator, inject electrolyte to form a battery.
[0152] Example 2
[0153] The difference between Example 2 and Example 1 is that the mass ratio of the quasi-single-crystal lithium manganate to the secondary spherical lithium manganate is 3:7;
[0154] MXene material is Ta4C3Tx;
[0155] The metal oxide is Nb2O5, and the other technical features are the same.
[0156] Example 3
[0157] The difference between Example 3 and Example 1 is that the mass ratio of the quasi-single-crystal lithium manganate to the secondary spherical lithium manganate is 1:9. The other technical features are the same.
[0158] Example 4
[0159] The difference between Example 4 and Example 1 is that the mass ratio of the quasi-single-crystal lithium manganate to the secondary spherical lithium manganate is 4:6. The other technical features are the same.
[0160] Example 5
[0161] The difference between Example 4 and Example 1 is that the mass ratio of the quasi-single-crystal lithium manganate to the secondary spherical lithium manganate is 5:5. The other technical features are the same.
[0162] Example 6
[0163] The difference between Example 6 and Example 1 is that:
[0164] Ti3C2T x The mass ratio with the first mixture is 1:100;
[0165] The mass ratio of WO3 to the first mixture is 1: 100. The other technical features are the same.
[0166] Example 7
[0167] The difference between Example 7 and Example 1 is that:
[0168] Ti3C2T x The mass ratio with the first mixture is 0.1:100;
[0169] The mass ratio of WO3 to the first mixture is 0.1: 100. The other technical features are the same.
[0170] Comparative Example 1
[0171] The difference between Comparative Example 1 and Example 1 is that no coating layer is provided on the surface of the quasi-single-crystal lithium manganate and the secondary spherical lithium manganate.
[0172] Comparative Example 2
[0173] The difference between Comparative Example 2 and Example 1 is that the positive electrode material contains only the second positive electrode active material.
[0174] Comparative Example 3
[0175] The difference between Comparative Example 3 and Example 1 is that the positive electrode material contains only the first positive electrode active material.
[0176] Comparative Example 4
[0177] The difference between Comparative Example 4 and Example 1 is that the coating layer only includes WO3.
[0178] Comparative Example 5
[0179] The difference between Comparative Example 5 and Example 1 is that the coating layer only includes Ti3C2T x .
[0180] Comparative experiment:
[0181] The batteries of Examples 1-7 and Comparative Examples 1-3 were tested as follows.
[0182] 1. Battery capacity retention rate after 200 cycles:
[0183] At a temperature of 45°C, charge at a current of 0.2C to a charging cut-off voltage of 4.2V, switch to constant voltage charging to a cut-off current of 0.05C, let stand for 0.5h, discharge at a current of 0.2C to a cut-off voltage of 3.0V, let stand for 0.5h, enter the next charge and discharge cycle, and so on, for a total of 200 charge and discharge cycles, 200 cycle retention rate = discharge capacity of the battery at the 200th cycle / first discharge capacity.
[0184] 2. Rate performance:
[0185] At a temperature of 45°C, the fully charged battery is discharged at a current of 0.1C to a cut-off voltage of 3.0V, and the capacity obtained by the test is C0;
[0186] At a temperature of 45°C, a fully charged battery is discharged at a current of 3C to a cut-off voltage of 3.0V. The capacity obtained by the test is C1, and C1 / C0 is the 3C discharge capacity retention rate below.
[0187] 3. Protective layer thickness test
[0188] Using a TEM electron microscope, ten different locations were selected to measure the thickness and the average value was taken.
[0189] 4. Compaction density test
[0190] Take the positive electrode plate, roll it, measure the thickness of the plate at five different positions, and get the compaction density according to the formula: compaction density (g / cm3) = surface density (mg / cm2) / thickness (μm).
[0191] 5. Discharge capacity test
[0192] At 25°C, the prepared battery was discharged at a constant current of 0.2C to a cut-off voltage of 3.0V, and the first discharge gram capacity of the battery was recorded.
[0193]
[0194]
[0195] Compared with the embodiments and comparative examples, the present application forms a coating layer on the surface of the quasi-single-crystalline lithium manganese oxide and the secondary spherical lithium manganese oxide, which can effectively prevent the quasi-single-crystalline lithium manganese oxide and the secondary spherical lithium manganese oxide from particle breakage during rolling and in the cycle of the battery, thereby ensuring the cycle stability of the lithium manganese oxide material and ensuring the good ion transport performance of the quasi-single-crystalline lithium manganese oxide material.
[0196] The battery's cycle performance and rate performance can be further improved by forming a composite coating of MXene materials and metal oxides on the surface of single-crystal lithium manganese oxide and secondary spherical lithium manganese oxide. The possible reason is that both MXene materials and metal oxides are resistant to HF corrosion, ensuring the stability of the positive electrode interface, so that the modified interface can form a more stable CEI film during the charge and discharge process, achieving a better isolation effect on the electrolyte and lithium manganese oxide materials; thirdly, the MXene material and metal oxide cooperate synergistically, which is beneficial to improve the ionic conductivity of the coating layer. The above is only a possible speculation on the mechanism and does not constitute a limitation on the scope of protection of this application.
[0197] Compared with Example 1 and Comparative Examples 2 and 3, the coated quasi-single-crystal lithium manganate and the secondary spherical lithium manganate are mixed. Since the two have a certain difference in particle size, the small quasi-single-crystal lithium manganate particles can be evenly filled into the gaps between the large secondary spherical lithium manganate particles, and then the combination of the two can effectively improve the compaction density of the positive electrode active material.
[0198] It is particularly important to point out that, for lithium-ion battery manufacturers and technicians in the same field, inspired by the above-mentioned technical solutions and embodiments, they can select or change the technical features to replace them to obtain a technical solution that is essentially the same as the present invention, and the lithium batteries manufactured thereby should fall within the scope of protection of the present invention.
Claims
1. A positive electrode active material, characterized in that The positive electrode active material includes a first positive electrode active material and a second positive electrode active material; The first positive electrode active material includes quasi-single-crystal lithium manganese oxide and a coating layer coated on the surface of the quasi-single-crystal lithium manganese oxide; The second positive electrode active material includes secondary spherical lithium manganese oxide and a coating layer coated on the surface of the secondary spherical lithium manganese oxide; The coating layer includes MXene material and metal oxide.
2. The positive electrode active material according to claim 1, characterized in that The MXene material includes any one of Ti3C2Tx, Nb2CTx, Ta4C3Tx or V4C3Tx, or a combination of at least two thereof.
3. The positive electrode active material according to claim 1, characterized in that The metal oxide includes at least one of MgO, Al2O3, Nb2O5, ZrO2, and WO3.
4. The positive electrode active material according to claim 1, characterized in that The general formula of the single-crystal lithium manganate is Li 1+ a Mn 2-a-b-c Al b B c O4; among which, 0.001≤a≤0.30, 0.001≤b≤0.2, 0.001≤c≤0.
1.
5. The positive electrode active material according to claim 1, characterized in that The general formula of the secondary spherical lithium manganate is Li 1+x Mn 2-x-y M y O4; wherein, 0.001≤x≤0.20, 0.001≤y≤0.3, and M includes at least two of Mg, Al, Nb, and Co.
6. The positive electrode active material according to claim 1, characterized in that The coating layer has a thickness of 10 to 100 nm.
7. The method for preparing the positive electrode material according to claim 1, characterized in that: The method comprises the following steps: 1) uniformly mixing the quasi-single-crystal lithium manganate and the secondary spherical lithium manganate to form a first mixture; 2) mixing the first mixture, MXene material, metal oxide and solvent to obtain a mixed solution; 3) spray drying the mixed solution to obtain a positive electrode active material.
8. The preparation method according to claim 7, characterized in that: The step 1) comprises uniformly mixing the quasi-single-crystal lithium manganate and the secondary spherical lithium manganate in a mass ratio of (1-4):(9-6).
9. A positive electrode, characterized in that The positive electrode includes the positive electrode active material as claimed in claim 1 .
10. A battery, characterized in that The battery comprises the positive electrode active material according to claim 1 or the positive electrode according to claim 9.
Citation Information
Patent Citations
High-voltage and single-crystal ternary positive electrode material and preparation method thereof
CN107293744A
Mxene-coated composite electrode material and preparation method therefor
CN107706372A
Lithium-rich manganese-based composite positive electrode material optimized by adopting Mxene and preparation method of lithium-rich manganese-based composite positive electrode material
CN114944481A
Porous MXene coated lithium ion battery positive electrode material and preparation method thereof
CN115763764A
Spinel-type lithium manganate, preparation method thereof, lithium-ion battery, and electrical apparatus
WO2024222955A1